Progressive muscle relaxation application (PURE App) for dysmenorrhea - Aldinda, Tharra Widadari; Sumarni, Sri; Mulyantoro, Donny Kristanto; Azam, Mahalul; Sudiyono, Sudiyono (MEDISAINS, 2022)
Background: The prevalence of primary dysmenorrhea in Indonesia is 54.89%. Progressive Muscle Relaxation (PMR) exercises have proven to decrease the symptoms of dysmenorrhea. Nowadays, the android application can be widely accessed anywhere and anytime, thus saving time and costs. There has never been a study that applies PMR, especially android-based dysmenorrhoea.Objective: The current study aimed to develop the PURE App, a PMR exercise android-based application, and to test the effectiveness of reducing the menstrual pain score of adolescents with primary dysmenorrhea.Method: This study conducted Research and Development (R&D), which consists of 4 stages, namely information collection, application design, expert validation and revision, and trial.Result: The PURE App has five features, ranging from pain screening to exercise. The trial results showed that the PURE App application effectively reduced menstrual pain in adolescents with dysmenorrhea. The treatment decreased pain score from 4.48±0.71 to 1.98±1.49 in the treatment group (p<0.001). The treatment group's post-measurement pain score was also significantly different compared to the control group, 1.98±1.49 and 4.90±1.10, respectively.Conclusion: The PURE App benefits teenagers, especially those with primary dysmenorrhea. This application will make it easier for teenagers to overcome pain because the exercises on the application can be accessed anytime and anywhere.